Therapeutic Management of Congestive Heart FailureSecondary to Dilated Cardiomyopathy in a Male LabradorDog: A Case Report - Bhuyan, Udipta; Sandilya, Anindita (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dilated cardiomyopathy (DCM) is characterized by significant systolic dysfunction and expansion of the  heart chambers (Oyama, 2015). In dogs, DCM is one of the  most prevalent acquired cardiovascular conditions. Since  idiopathic DCM accounts for the majority of cases in dogs,  most treatments are categorized as ‘‘Band-Aid therapies,’’  which temporarily relieve symptoms but don’t address the  underlying source of the illness (Sanderson, 2006). Without  any indication of heart symptoms, the concealed stage of this  illness is typified by structural or electrical alterations. The  main morphologic signs of systolic dysfunction are left and  rarely right ventricular dilatation in systole and later diastole.  Ventricular premature complexes are the most common  type of electrical abnormalities (Wess et al., 2017). Clinical  indicators of congestive heart failure (CHF), such as elevated  respiratory rate, dyspnoea, coughing, or exercise intolerance,  are what define the overt stage of the condition (Friederich et  al., 2020). The present report describes a case of congestive  heart failure secondary to dilated cardiomyopathy in a  Labrador dog and its successful therapeutic management.
Keywords: Dilated Cardiomyopathy; Congestive Heart Failure; Pimobendan